ANALISIS PENGARUH INVESTASI TERHADAP PENDAPATAN ASLI DAERAH DAN PERTUMBUHAN EKONOMI DI PROVINSI BALI - PRATIWI, I GUSTI AYU MADE AGUNG MAS ANDRIANI (Universitas Mahasaraswati K. Mataram, 2023)
Macroeconomic problems in the long term are often associated with economic growth problems. Economic growth is an indicator of development success. The higher economic growth, usually the higher the welfare of society. Bali Province is one of the provinces in Indonesia that has experienced turbulent economic growth over the last five years, one of the reasons being the Covid-19 pandemic. Moreover, Bali Province has made the tourism sector the main sector supporting the economy in the region. This research is focused on discussing the investment picture that is linked to local revenue and economic growth in Bali Province. The objectives of this research include: 1) to determine the effect of investment on local revenue and economic growth in Bali Province; 2) to determine the effect of local revenue on economic growth in Bali Province; and 3) to determine the role of local original income in mediating the influence of investment on economic growth in Bali Province. The approach used in this research is a quantitative approach. This research uses secondary data obtained from BPS Bali Province. The data used in this research is time series data for each Regency/City in Bali Province from 2013-2022. This research uses data processing tools, namely Microsoft Excel and SPSS. The research results show that: 1) investment has a positive and significant effect on local revenue in Bali Province; 2) investment and local revenue have a positive but not significant effect on economic growth in Bali Province; and 3) local original income mediates the effect of investment on economic growth in Bali Province.